Heterologous effect of influenza vaccination on molluscum contagiosum infection; a case report of siblings - Michelle L. Lawson; Sofia M. Szari; Thomas M. Beachkofsky; David E. Hrncir (BMC, 2023)
Abstract Background Molluscum contagiosum virus (MCV) is a benign, common cutaneous infection predominantly affecting the younger pediatric population. Traditional treatments may be time consuming with variable efficacy. Time to spontaneous resolution is variable and treatment is often sought to shorten duration of infection, prevent further autoinoculation, prevent infectious spread to others and treat cosmetic intolerability. Case presentation We present the case of two patients with complete, simultaneous clearance of their molluscum contagiosum infections after receiving a routine 2018 quadrivalent influenza vaccination. Neither patient has had recurrence of molluscum contagiosum or permanent scarring. We review trials of intralesional immunotherapy in treatment of cutaneous infections to theorize the mechanism of MCV infection clearance post influenza vaccination. Conclusion We propose a delayed-type hypersensitivity reaction was induced as a heterologous effect of the influenza vaccination, similar to that seen in current immunotherapy treatments. This is the first reported case of MCV-directed immune reaction with infection clearance after influenza vaccination.